The Role of Building Technology in Obtaining Sustainable Place Selected buildings in Sulaimani, Kurdistan Region, Iraq-as case study - Ali, Alan Faraydoon (Sulaimani Journal for Engineering Sciences, 2019)
The distinctive ecological issues from pollution, exhaustion of vitality and assets, pushed the sustainability wonder through the down to earth and theoretical application to take a vast part in the contemporary worldwide patterns, as a way to discover answers for the world natural strains and its results. As the supportable engineering associated unequivocally with the biological system on one hand, and to different frameworks identified with the natural frameworks, from alternate, this has turned out to be a standout progressive the most dynamic topics in feasible applications and research. This research was to simulate this idea, with a review to the likelihood of applying manageability standards in contemporary engineering and the impact of the utilization of innovation in accomplishing this maintainability, which will prompt review the how and the approaches to accomplish sustainability in architecture and how to utilize the innovation as the potential instruments of this time in accomplishing these manageability, offering intending to the indigenous habitat as to keep up the soul of the place. The utilization of innovation as an instrument of the advanced period to accomplish economical design, the association with nature, and understanding the idea of "soul of the place"; lead us to concentrate the likelihood of utilizing innovation and IT to see more about the importance of place and maintainability in the current time to make a positive society interface with the contemporary necessities, and furthermore with the regular habitat they live in . This research aims to reach to the clarify the indicators of the Building Technology and Sustainable spirit of place, then the research will analyze these indicators in different public projects in Sulaimani city by the analyzing the average of the questionnaires answers , then reaching the conclusions and the recommendations of the research.
Keywords: sustainability; building technology; the place; the spirit of the place